Facile and Efficient Welding of Silver Nanowires Based on UVA‐Induced Nanoscale Photothermal Process for Roll‐to‐Roll Manufacturing of High‐Performance Transparent Conducting Films. Issue 3 (10th December 2018) - Liang, Xianwen; Lu, Jibao; Zhao, Tao; Yu, Xuecheng; Jiang, Qingshan; Hu, Yougen; Zhu, Pengli; Sun, Rong; Wong, Ching‐Ping
Abstract: The continuous, large‐area solution‐processed production of silver nanowire (AgNW) transparent conducting films with outstanding optoelectronic and mechanical performance remains a challenge. Here, efficient welding of AgNWs is demonstrated using ultraviolet A (UVA) with the specific wavelength range from ≈320 to ≈400 nm based on a nanoscale photothermal process. The AgNW welding shows a self‐terminating and self‐limiting nature, and sensitivity to diameter of AgNWs. Sheet resistance of the UVA‐illuminated (UVAI) AgNW films rapidly drops within 2 min without loss of transmittance. For the UVAI AgNW (30 nm in diameter) film, decrement of sheet resistance approaches three orders of magnitude (≈10 5 –10 2 Ohm sq −1 ) with original transmittance being (97%) retained, which significantly enhances its optoelectronic properties. Enhanced mechanical flexibility, electromagnetic interference (EMI) shielding effectiveness (SE), and heating performance are obtained in the UVAI AgNW films. The SE and plateau temperature of the AgNW film increase to 25 dB and 50 °C after illumination, respectively. Smart window, transparent heater, and triboelectric nanogenerator based on the UVAI AgNW film demonstrate its versatile applications in optoelectronics. Finally, the welding method is easily integrated into a roll‐to‐roll process to manufacture AgNW film with a low sheet resistance of 25 Ohm sq −1 and a high transmittance of 90%, and excellent flexibility. Abstract : A convenient, efficient silver nanowire (AgNW) welding strategy based on the ultraviolet A (UVA)‐induced nanoscale photothermal process significantly enhances the optoelectronic, mechanical, electromagnetic interference shielding and heating performance of AgNW films, and can be easily integrated into a continuous, large‐area roll‐to‐roll process to manufacture high‐performance AgNW transparent conducting films, facilitating the AgNW films to widely meet practical applications in optoelectronics.